Comparison of Some Somatic and Reproductive Characters for Tow Brood Stock of Cyprinus Carpio L. (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Studies have been done in seven hatchenis in in Mahawil district/Babil  from the period  15/3 to 15/5 to identify the body and reproductive characteristics between common carp brood stock which was imported in 2009 containing this shiny line of scales that exists dorsal fin of carp and which is without shiny line of scales was imported in 1982. Body characteristic results showed significant difference P ‹ 0.05 between two brood stock  according to body depth/standard length feature,  so they reached an average of this feature in common carp shiny line of scales 0.003 ± 0.389 higher than those containing no shiny line reached 0.002 ± 0.369, whereas no significant differences was shown between two brood stock for fish weight and head length/ standard length. Reproductive characteristic study showed significant difference P ‹ 0.05 for shiny line brood stock for each  total eggs weight(gm) , eggs number /gm eggs , eggs weight/kg fish and fertilization percentage characteristic , which reached an average of  26.62 ± 520.28, 4.46 ± 764.60, 94.76 ± 159.2, 0.33 ± 82.91 respectively, higher than of those without shiny line brood stock which reached average of 21.32 ± 461.42, 4.44 ± 711.15, 4.42 ± 147.73 respectively, whereas significant difference was shown in egg diameter  characteristic for containing no shiny line brood stock which reached 0.01 ± 1.411 where brood stock of shiny line reached average of 0.01 ± 1.38 and no significant differences were showed between two brood stock in eggs number/ kg fish. That an increase of crossbreeding between different lines for common carp of brood stock do in improve somatic  and reproductive characteristics  of inbreeding and prevents deteriorating.